2020
DOI: 10.3389/fpls.2020.575015
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genome-Wide Analysis of Thaumatin-Like Gene Family in Four Cotton Species and Functional Identification of GhTLP19 Involved in Regulating Tolerance to Verticillium dahlia and Drought

Abstract: Thaumatin-like proteins (TLPs) present in the form of large multigene families play important roles in biotic stress and abiotic stress. However, there has been no systematic analysis of the TLPs in cotton. In this study, comprehensive identification and evolutionary analysis of TLPs in four species of cotton were conducted. In total, 50, 48, 91, and 90 homologous sequences were identified in Gossypium raimondii, G. arboreum, G. barbadense, and G. hirsutum, respectively. Gene structure, protein motifs, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 78 publications
(103 reference statements)
3
35
0
Order By: Relevance
“…Further, the expression profiling of TLPs under various tissues and developmental stages also advocated the putative involvement of these genes in development of vegetative and reproductive tissues. Similar expression trend in various plant tissues and their role in reproductive tissues like flowers and seeds has also been reported in earlier studies, for instance, TLP genes in Gossypium hirsutum, also showed their varied expression pattern in vegetative as well as in reproductive organs [18,56,71]. The role of TLP genes in fungal resistance has been reported in earlier studies against numerous pathogens including Fusarium sp.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Further, the expression profiling of TLPs under various tissues and developmental stages also advocated the putative involvement of these genes in development of vegetative and reproductive tissues. Similar expression trend in various plant tissues and their role in reproductive tissues like flowers and seeds has also been reported in earlier studies, for instance, TLP genes in Gossypium hirsutum, also showed their varied expression pattern in vegetative as well as in reproductive organs [18,56,71]. The role of TLP genes in fungal resistance has been reported in earlier studies against numerous pathogens including Fusarium sp.…”
supporting
confidence: 85%
“…Expression analysis of genes is a significant way to understand their involvement in various developmental and physiological processes. Previously, TLPs are reported to be involved in plant growth and developmental processes [56,57]. Therefore, we performed the expression analysis of TLPs under various tissues and their developmental stages.…”
Section: Expression Profiling Of the Tlp Genes Under Different Tissues And Developmental Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over-expression of the PeTLP gene in transgenic poplars showed enhanced resistance against Marssonina brunnea [23]. In addition, some TLP genes have also been reported to confer tolerance to abiotic stresses such as drought, salt, and low temperatures in transgenic plants [17,21,24,25].…”
Section: Introductionmentioning
confidence: 99%